2008
DOI: 10.1103/physrevc.77.024318
|View full text |Cite
|
Sign up to set email alerts
|

Giant dipole resonance width in nuclei near Sn at low temperature and high angular momentum

Abstract: High energy γ-rays in coincidence with low energy yrast γ-rays have been measured from 113 Sb, at excitation energies of 109 and 122 MeV, formed by bombarding 20 Ne on 93 Nb at projectile energies of 145 and 160 MeV respectively to study the role of angular momentum (J) and temperature (T) over Giant Dipole Resonance (GDR) width (Γ). The maximum populated angular momenta for fusion were 67h and 73h respectively for the above-mentioned beam energies. The high energy photons were detected using a Large Area Modu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Fig. 1 Schematic view of the experimental setup for the LAMBDA spectrometer in a 7 × 7 matrix arrangment along with the low energy γ -ray multiplicity filter [21] In the early experiments NaI(Tl) detectors were used, mainly because they were readily available. One of the main sources of background in these experiments is due to neutrons which can be separated from γ -rays by a time of flight measurement and NaI(Tl) exhibits mediocre timing properties.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 1 Schematic view of the experimental setup for the LAMBDA spectrometer in a 7 × 7 matrix arrangment along with the low energy γ -ray multiplicity filter [21] In the early experiments NaI(Tl) detectors were used, mainly because they were readily available. One of the main sources of background in these experiments is due to neutrons which can be separated from γ -rays by a time of flight measurement and NaI(Tl) exhibits mediocre timing properties.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Figure 1 shows a schematic view of a typical set up for such low energy experiments taken from Ref. [21].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average temperature is defined as 〈 〉 T =Σ Σ w T w i i i , where w i is the weight for the ith step in decay chain and was calculated as the γ-ray yield in the energy range of 12-25 MeV. A few authors have reported an 'effective' temperature (T eff ) [12,17,50], which is defined as the temperature at which there is 50% of the high energy γ-ray yield (12)(13)(14)(15)(16)(17)(18)(19)(20) which is emitted between the threshold temperature (below which there is no significant change in GDR width) and the temperature of the initial compound nucleus. The effective temperature, in turn, considers only GDR contributing events in the decay cascade and thus, the average temperature 〈 〉 T in present context is similar to T eff .…”
Section: Imentioning
confidence: 99%
“…In the past few years, a large number of experiments have been dedicated to study the evolution of GDR widths with spin and temperature. Several authors have reported the measurement of GDR widths at finite temperatures in different mass regions, and these measurements could be categorized as low temperature measurements (below 1.5 MeV) [6][7][8][9][10][11][12][13], moderate temperature measurements (1.5-2.5 MeV) [14,15], and high temperature measurements (above 2.5 MeV) [16][17][18]. The general experimental method adopted in these experiments is to detect high energy GDR γ-rays in coincidence with low energy γ-ray multiplicity, which could be related to the total angular momentum of the nucleus.…”
Section: Introductionmentioning
confidence: 99%